Scheduling no-wait production with time windows and flexible processing times. - Chauvet, F. (IEEE Transactions on robotics and automation)
This paper presents a low-complexity algorithm for online job scheduling at workcenters along a given route in a manufacturing system. At each workcenter, the job has to be processed by any one of a given set of identical machines. Each machine has a preset schedule of operations, leaving out time-windows during which the job's processing must be scheduled. The manufacturing system has no internal buffers and the job cannot wait between two consecutive operations. There is some flexibility in the job's processing times, which must be confined to given time intervals. The scheduling algorithm minimizes the job's completion time, and it is executable in real time whenever the job requirement is generated